KONDISI EKSISTING TAHUN 2016 PELAYANAN RUSUNAWA RAWA BEBEK DI DKI JAKARTA - Retnowati WD Tuti (SWATANTRA, 2017)
Public service in Indonesia is known to be of poor quality. This applies also for services of regional government for residents of leased flats  (Rusunawa) especially those who were from relocation programs. DKI Jakarta Provincial Government  relocates citizens to live in leased flats in order to manage urban development to increase prosperity of DKI Jakarta citizens. This involved restructuring of government land illegally occupied by citizens where the citizens do not have the land certificates. These  citizens are relocated to low-cost leased flats (Rusunawa) in Rawa Bebek.  Citizens hurt by forced relocations even under threats need good service to be able to live in Rusunawa Rawa Bebek, this community must be able to adapt from living in the old horizontal place to the new vertical place. Of course, there are many problems faced by Flats Management Unit (UPRS) regarding the relocated low-income citizens. Other than that, the flats  were  new  buildings that have not been occupied before. These problems arised from the residents, buildings, managers and the surroundings. Aims of the research are 1) to analyse the exis- ting conditions of services in Rusunawa Rawa Be- bek 2) to find supporting and impeding factors of services in Rusunawa Rawa Bebek. Analysis blade used are 14 elements of citizen satisfaction indicators to measure rusunawa residents’ satisfactions: Service Procedures; Service Requirements; Clarity of the names and  parts of the job; Officer discipline; Officer responsibility; Officer ability; Officer Responsiveness; Service fairness; Officer CourtesyKeywords: service quality, Rusunawa